Troubleshooting of the beam dump problem caused by helium vessel pressure fluctuation during the cryogenic adsorber regeneration process of a superconducting RF system for synchrotron user facilities. (1st August 2022) - Joo, Youngdo; Sohn, Younguk; Park, Sehwan; Lee, Mujin; Kim, Junghoon; Lee, Yongseok; Lee, Mooneon; Park, Insoo
Abstract: The Pohang Light Source-II (PLS-II) is a synchrotron user-service facility that should provide a user-service period of 190 days per year with stable operation. A series of beam dump problems related to the superconducting radio-frequency (SRF) system but of unknown cause occurred twenty-five times from 2016 to 2018, which severely degraded the stable operation of the PLS-II and the SRF system. Intensive investigation has shown that the relevant beam dumps occurred when the helium (He) flow control valves operated momentarily during the adsorber regeneration process of the cryogenic system. As the control valves operate momentarily, the He vessel pressure of the cryomodule instantaneously fluctuates, and the resonance frequency of the SRF cavity accordingly changes. If the instantaneous change in the resonance frequency is larger than the low-level RF (LLRF) control ability, then incorrect handling of LLRF control occurs, resulting in a beam dump. The instantaneous changes in the He vessel pressure occur via three different mechanisms. Solutions for each beam dump mechanism were proposed and implemented. After each solution was carried out, no beam dump occurred during the adsorber regeneration process. The relation between the He vessel pressure and the resonance frequency of the SRF cavity was also studied to see how the solution works.